Câu hỏi

Chứng minh đẳng thức:                     

\({\left( {a + b + c} \right)^2} + {a^2} + {b^2} + {c^2} = {\left( {a + b} \right)^2} + {\left( {b + c} \right)^2} + {\left( {c + a} \right)^2}\)

  • A \({\left( {a + b + c} \right)^2}= {\left( {a + b} \right)^2} + {\left( {b + c} \right)^2} + {\left( {a + c} \right)^2}\)
  • B \({\left( {a + b + c} \right)^2} + {a^2} + {b^2} + {c^2}= {\left( {a + b} \right)^2} + {\left( {b + c} \right)^2} + {\left( {a + c} \right)^2}\)
  • C \({\left( {a + b + c} \right)^2}= {\left( {a + b} \right)^2} + {\left( {b + c} \right)^2} + {\left( {a + c} \right)^2} + {a^2} + {b^2} + {c^2}\)
  • D \({\left( {a + b + c} \right)^2} + {a^2} + {b^2} + {c^2}= 2{\left( {a + b} \right)^2} + 2{\left( {b + c} \right)^2} + 2{\left( {a + c} \right)^2}\)

Lời giải chi tiết:

Hướng dẫn giải chi tiết

 

\(\begin{array}{l}VT = {\left( {a + b + c} \right)^2} + {a^2} + {b^2} + {c^2}\\VT = {a^2} + {b^2} + {c^2} + 2ab + 2bc + 2ac + {a^2} + {b^2} + {c^2}\\VT = \left( {{a^2} + 2ab + {b^2}} \right) + \left( {{b^2} + 2bc + {c^2}} \right) + \left( {{a^2} + 2ac + {c^2}} \right)\\VT = {\left( {a + b} \right)^2} + {\left( {b + c} \right)^2} + {\left( {a + c} \right)^2}\\ \Rightarrow VT = VP\end{array}\)

\(\Rightarrow \) Đpcm


Luyện Bài Tập Trắc nghiệm Toán 8 - Xem ngay